Warhogs : A History of War Profits in America - Brandes, Stuart D. (Book collections on Project MUSE., 2015)
The Puritans condemned war profiteering as a ""Provoking Evil, "" George Washington feared that it would ruin the Revolution, and Franklin D. Roosevelt promised many times that he would never permit the rise of another crop of ""war millionaires."" Yet on every occasion that American soldiers and sailors served and sacrificed in the field and on the sea, other Americans cheerfully enhanced their personal wealth by exploiting every opportunity that wartime circumstances presented. In Warhogs, Stuart D. Brandes masterfully blends intellectual, economic, and military history into a fascinating dis.